Committing to transform food systems: Responsiveness of food systems transformation pledges by African governments to the WHO priority food systems policies and food-related CAADP biennial review performance categories - Nanema, Silver; Amevinya, Gideon Senyo; Laar, Amos (AKADEMIYA2063, 2023)
For several decades, Africa’s food security situation has been dire. However, that dire state has recently been complicated by rising rates of overweight and obesity and other diet-related noncommunicable diseases. By 2030, noncommunicable diseases are predicted to become the leading cause of death on the continent amid other pandemic and economic challenges. Several interventions have been deployed to address the emerging challenges. African heads of state and government have been committing, declaring, pledging, and developing national and regional nutrition strategies, and they have envisioned the Africa they would want by 2063—the African Union’s Agenda 2063. Other actions include commitments made as part of the 2021 United Nations Food Systems Summit. With less than a decade to go to meet the 2030 agenda for transforming food systems in a sustainable way, we must ask whether these new commitments and recommitments can fulfill that promise. In this chapter, we assess the responsiveness of some African nations’ commitments to (1) the World Health Organization’s food priority policy actions, and (2) select Comprehensive Africa Agriculture Development Programme Biennial Review performance categories. Both actions are touted as game changers—actions that have the potential to pave the way for the needed changes in Africa’s food systems.